2023
DOI: 10.4103/ija.ija_31_23
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in chronic pain medicine

Abstract: Chronic pain presents as an unequalled challenge for physicians, owing to the complexity of biochemical and biological pathways involved in pain transmission and high variability of pain perception among individuals. Often, there is an inadequate response to conservative treatment, and opioid treatment has its own drawbacks, such as side effects and opioid dependence. Hence, novel strategies have evolved for the effective and safe management of chronic pain. Radiofrequency technique, regenerative biomaterial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the present study, we found a reduction in pain levels since all patients showed a significant decrease in mean VAS score of pain after 2 weeks, 1 month, 3 months, and 6 months of nanofat injection compared to that preoperatively. Many studies that used ADSCs for pain management show the same results, concluding that stem cells effectively reduce pain 31,32 …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the present study, we found a reduction in pain levels since all patients showed a significant decrease in mean VAS score of pain after 2 weeks, 1 month, 3 months, and 6 months of nanofat injection compared to that preoperatively. Many studies that used ADSCs for pain management show the same results, concluding that stem cells effectively reduce pain 31,32 …”
Section: Discussionmentioning
confidence: 85%
“…Many studies that used ADSCs for pain management show the same results, concluding that stem cells effectively reduce pain. 31,32 Pain reduction in those patients is related to the ADSCs exhibiting immunosuppressive characteristics and minimal immunogenicity, making them excellent for transplantation to painful and injured sites; also, their ability to release trophic factors improves the therapeutic and corrective outcome. 33,34 Along with the reduction in pain VAS score, improvement in MMO was shown in the result of this study at all times of assessment postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In ocular conditions, sustained release drug-delivery systems enhance the efficacy of treatments for diseases like glaucoma and macular degeneration. Overall, biomaterials revolutionized the pain management through the development of localized, sustained-release drug-delivery systems [234][235][236]. These systems can be implanted or injected near the source of pain, ensuring that analgesic medications are delivered directly to the affected area, reducing the potential for systemic side effects and dependency.…”
Section: Immunogenicitymentioning
confidence: 99%
“…σRs can be classified into two subtypes of, σ1R and σ2R, which exhibit distinct molecular structure, distribution, and pharmacological profile. σ1R is expressed in several cell types, including neurons and astrocytes, playing a crucial role in multiple cellular functions, such as calcium signalling, lipid metabolism, protein folding and intercellular communication [ 17 ]. σ2R is also expressed in the CNS and in peripheral organs, gaining significant attention due to its role in several cellular processes, such as cell growth, differentiation and proliferation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%